Теоретичні підходи до розкриття економічної сутності регулювання - Єкель, Г. В.; Iekel, G. V. (Видавництво Львівської політехніки, 2017)
Наведено погляди різних науковців стосовно визначення змісту дефініції “регулювання”. Встановлено, що це поняття похідне від “регулювати”, і саме так представлене у багатьох джерелах. З огляду на це, проаналізовано багато наукових джерел, на основі яких виявлено спільні ознаки досліджуваних категорій. Запропоновано авторське визначення категорії “регулювати”. Аналіз праць вітчизняних та зарубіжних учених стосовно змістового наповнення поняття “регулювання” дав змогу виявити, що його варто розглядати у кількох аспектах. Встановлено, що категорії “регулювання” притаманні такі ознаки: системність, контроль, організація, нормативність, синергізм, направленість, гнучкість.

The article presented the views of different scholars on the definition content of "regulation". This concept was derived from "regulate" and that has been represented in many sources were found. It was considered the author of a number of scientific resources were analyzed and identified the major common features in the studied categories. The basic part of research was divided into two parts : focus on regulation as a function of component management, and studying its subtypes on governmental level. The purpose of the article was to study the semantic content category "regulation". The main goals of research were the following: - to analyze different scientific sources on defining content "regulate"; - to identify common features in the study category; - to propose their own definition "regulate". Research has shown that most scientists are inclined to believe that "regulate" - means: 1) to organize; 2) to achieve normal operation mechanism; 3) to ensure the smooth interaction of components; 4) to subordinate to certain rules; 5) to control something. According to the author, to "regulate" the means to organize a set of objects according to given rules, regulations, procedures for specified results, while ensuring the smooth interaction of components, by monitoring and correction in case of deviation from the desired direction. The author established that categories "regulation" has the following characteristics: consistency, control, organization, regulatory, synergy, orientation, flexibility. Consistency is to establish a proper mechanism of interaction of parts, and this is only possible if they staged a joint operation with clear allocation of functions and powers of each component. Control means using certain rules, principles, methods and ways to monitor the condition of produce and make adjustments in operations in case of deviation from the set parameters. Orientation - activity in certain defined subject area. Organization - is the ordering of certain events and processes through regulation. Synergy - the effect of the coordinated interaction of components. Normativity - means submission to certain rules, norms The flexibility provided in adjusting of the object in the desired direction. Our studies provided an opportunity to make some following conclusions: regulation - should be viewed in several ways: as a form of management, which includes the impact of the subject to the object in order to achieve certain goals; as a function of management aimed at implementation of operational tasks and correct deviations that occur during work on the basis of monitoring and analysis activities; as the means and mechanism of subordination subject to certain laws (rule, order), as the principle or rule that is subject to certain objects. According to the author's point of view the studied category plays an important role in process-structural and administrative management. That is, to build a mechanism to regulate agriculture, which would have combined a effective interaction institutional environment and market instruments aimed our further research.
The theoretical approaches to determine the economic essence of “regulation”
Keywords: упорядковувати; регулювати; управління; система; правило; manage; regulate; control; system; rule; 338